The Implementation Of Discipline And Responsibility Through Procedure Texts In High Schools Students’ Textbooks - Siti Rochmiyati; Die Bhakti Wardoyo Putro; Eni Lestari (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2021)
School is the place where younger generations are educated both intellectually and characteristically. Through schooling, students are projected to able to develop their potential so that they are capable of living independently in society and pursue higher education. To achieve this objective, students are required to establish, among others, the character of discipline and responsibility since both knowledge transfer and character building are inseparable in teaching-learning processes. During the pandemic, however, the teaching-learning process is facing a new challenge by which both teachers and students must carry the process through online courses. Alternatively, the character of discipline and responsibility can be introduced to students through procedure texts. Procedure text is a type of text whose purpose is to instruct in how to do something through a sequence of steps. Procedure text requires students to ‘get something done’ by the mean of strictly following the steps prescribed in the text. This qualification demand students performing the character of discipline and responsibility so that the goal could be achieved accordingly. Moreover, the teacher are to build the character of discipline and responsibility from an early age. Students' discipline and responsibility improvement necessitate students' awareness as well as both parents' and teachers’ guidance.